Escolas e territórios : aspectos da desigualdade - Cabral, Ana Karina Santos dos (2020)
This research establishes a cross between the themes of education, school inequality and territory of belonging. Through secondary data and participant observation, different school realities are described in different territories from the city of Porto Alegre, observing in addition to classrooms, teaching and student living spaces, patios, corridors and surroundings of two public schools. Secondary data point to school inequalities and present rankings produced from the results of tests that measure student performance such as Prova Brasil and ENEM. The qualitative research highlights the specificity and challenges represented by the social and economic profile of students on the night shift, the external interferences that modify the school routine and the importance of the school location and the territories of students' belonging in the configuration of inequalities in different levels.